Exploring the effectiveness of couples interventions for adults living with a chronic physical illness: A systematic review. Issue 7 (July 2017) - Berry, Emma; Davies, Mark; Dempster, Martin
Highlights: Couples interventions can often be more beneficial than the patient-only equivalent. Therapeutic outcomes for couples are strongly contingent on intervention approach. Many chronic illnesses and ethnicities remain understudied in couples research. Abstract: Objective: Partners have a significant role in a person's ability to adjust to a chronic physical illness, which warrants their inclusion in couples interventions. However to deliver more specific, tailored support it is necessary to explore which types of couples interventions are most effective across certain chronic illness populations and outcomes. Methods: Five databases were searched using selected terms. Thirty-five articles met the eligibility criteria for inclusion. Results: The majority of studies were from the US, and most interventions targeted cancer populations. Couples interventions fell into two categories according to therapeutic approach; Cognitive Behavioural Skills Training (CBST) and Relationship Counselling (RC). When compared with a patient-only intervention or controls, CBST interventions effectively targeted behavioural, physical/somatic and cognitive outcomes, while RC more effectively targeted interpersonal outcomes. Conclusion: Couples interventions can be more effective than patient-only interventions or controls across various patient and partner outcomes. Couples interventions tend to favour a skills-based or a relationship-based approach, which strongly influences the types outcomes effectively targeted. Practice implications: Our findings suggest it could be therapeutically useful to integrate these two approaches to more holistically support couples living with chronic illness. We also identify the need to target understudied illness groups and ethnicities.